Solvent-driven morphological and electrochemical enhancements in catalyst layers for proton exchange membrane water electrolysis - Park, Jong-Hyeok; Heo, Jiyoung; Park, Hyun S.; Park, Jin-Soo (Elsevier BV, 2025)
This study investigates the impact of dispersing solvents on the performance and durability of the catalyst layer (CL) in proton exchange membrane water electrolysis (PEMWE). The findings show that solvent selection significantly affects the dispersion behavior of the ionomer, which in turn influences the structure of the catalyst ink and the homogeneity of the CL. Variations in dispersity lead to differences in CL morphology and electrochemical performance. Solvents with more negative solvation energy, such as ethylene glycol (EG) and propylene glycol (PG), promoted better dispersion of the ionomer and catalyst, resulting in more uniform CL structures. This improved homogeneity contributed to enhanced electrochemical performance, with EG- and PG-based CLs achieving high current densities of 2503.20 and 2168.75 mA/cm2 at 1.9 V, respectively. The superior performance is attributed to the well-connected, uniform morphology made possible by the high dispersing capability of these solvents. Furthermore, solvent type also played a key role in durability, affecting degradation slopes and charge transfer resistance (CTR) increases. Among the tested solvents, PG exhibited the best stability, with the lowest degradation slope (314 mu V/h) and smallest CTR increase (26.67 %). These results emphasize the importance of solvent selection in optimizing both performance and durability in PEMWE CLs.